Analisis Efektivitas Sistem Pengendalian Manajemen Penggajian Pada PT. Aura Mandiri - febi aleyda yahya (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2021)
ABSTRACT The current era requires speed and accuracy in making decisions, so that potential factors of production are needed. The existence of human resources as the main factor, then provides a reward for the achievements achieved in the form of salary. Provision of ineffective salaries can cause problems for the company, especially in relation to HR performance. To avoid this, it is necessary to control payroll management that ensures the fulfillment of the rights of workers (employees).The reward given by the company for the achievements of the workforce (employees) is salary. Ineffective payrolls cause problems for companies related to the performance of human resources (HR). To avoid this problem, a payroll management control system is needed to protect the rights of workers (employees). This study aims to analyze the effectiveness of the payroll management control system at PT. Aura Mandiri. The research method used is descriptive qualitative method. The results showed that the payroll management control system at PT. Aura Mandiri is quite effective because the company carries out procedures from start to finish and there are some other functions that are inadequate, namely the employee attendance list is still manual and has not taken advantage of more sophisticated technology, for example using a fingerprint system. Keyword : Effectiveness, Management Control System, Payroll